The Process Of Enculturation: The Nepali Community In Darjeeling Hills And Terai In North Bengal. - Mangar, Asudha (International Journal of Psychosocial Rehabilitation, 2020)
The social environment of any human group plunges into culture. It is the culture that guides the people-—what to eat, what to do and how to do it, how to talk, and how to think. Human behaviors are grossly determined by culture as the individuals are born, raised, and live in it. A person can never be free from cultural influences. Melville J. Herskovits, in his book Man and His Works (1947), tried to relate culture and individual in terms of enculturation. Enculturation is the process by which an individual learns the forms of conduct acceptable to his group. He points out that in diffusion, the transmission of culture is a gradual process of culture change of which acculturation is one expression, which occurs when any two are in historic contact. According to Felix-Keesing, “Culture change may be defined broadly as a reformation in group behavior; such reformation may be seen occurring from the level of individual experience, as being an innovator or accepting an innovation to that of the total functional and integral setting of a culture system.” The Nepali community is comprised of various castes, viz., Brahmin, Chhetri, Newar, Mangar, Gurung, Rai, Limbu, Subba, Bhujel, Damai, Kami, Sarki, etc. With the growing consciousness and identity aspirations, a resurgence of culture of the respective caste occurred in the latter half of the 20th century. Since the 1990s, each community devoted themselves to preparing their respective qualifying paper as a ‘tribe’ based on the features laid down by the Government of India. The urge for preservation of culture transforms cultural aspects of various communities in the region, and a change was evident. The paper, hence, tries to reflect the basic cultural transformation of a few Nepali castes and its effect on their cultural practices.